2005
DOI: 10.1016/j.rie.2005.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Mixed oligopoly and the choice of capacity

Abstract: We analyze the capacity choice of firms under different time structures in a mixed oligopoly market, in which firms decide not only production quantities but also capacity scales. We show that the public firm never chooses excess capacity, while the private firm never chooses under capacity under all possible strategic environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 12 publications
0
38
3
Order By: Relevance
“…They show that, whereas a profit-maximizing private firm chooses overcapacity, a welfare-maximizing public firm chooses undercapacity. Lu and Poddar [15] investigate the capacity choice of firms in mixed duopoly market under the environments of sequential or simultaneous capacity choice. They conclude that the public firm never chooses overinvestment in capacity and the private firm never chooses underinvestment in capacity.…”
Section: Equilibriummentioning
confidence: 99%
“…They show that, whereas a profit-maximizing private firm chooses overcapacity, a welfare-maximizing public firm chooses undercapacity. Lu and Poddar [15] investigate the capacity choice of firms in mixed duopoly market under the environments of sequential or simultaneous capacity choice. They conclude that the public firm never chooses overinvestment in capacity and the private firm never chooses underinvestment in capacity.…”
Section: Equilibriummentioning
confidence: 99%
“…6 Note that Nakamura and Saito [28] which considered the quantitysetting mixed duopoly with the degree of importance of the private firm's relative performance showed that the difference between the output and capacity levels of the public firm also changes in accordance with the degree of importance of the private firm's relative performance, even though the area of the demand parameter corresponds to the case wherein the relation between the products by both the public firm and the private firm is substitutable. In addition, another strand of the capacity choice problems in a mixed oligopoly, comprising Lu and Poddar [30], Lu and Poddar [31], Lu and Poddar [32], and Bár-cena-Ruiz and Garzón [33], too focused on several kinds of economic factors. Lu and Poddar [30] and Lu and Poddar [31] explored the effects of a change in competition style to sequential-move competition and of the introduction of demand uncertainty, respectively, on the capacity choice of both the public firm and the private firm.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another strand of the capacity choice problems in a mixed oligopoly, comprising Lu and Poddar [30], Lu and Poddar [31], Lu and Poddar [32], and Bár-cena-Ruiz and Garzón [33], too focused on several kinds of economic factors. Lu and Poddar [30] and Lu and Poddar [31] explored the effects of a change in competition style to sequential-move competition and of the introduction of demand uncertainty, respectively, on the capacity choice of both the public firm and the private firm. Furthermore, Lu and Poddar [32] and Bárcena-Ruiz and Garzón [33] investigated a game with endogenous timing of the sequential choice of the capacity levels and output levels of both the public firm and the private firm on the basis of an observable delay game presented in Hamilton and Slutsky [34].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we show that under the assumption that the products of the public firm and the private firm are restricted to being substitutable, the public firm sets over- 2 More recently, in capacity choice in a mixed oligopoly, Lu and Poddar [8] and Lu and Poddar [9] analyzed the case of each firm's sequential move and the case of demand uncertainty, respectively. Subsequently, Tomaru et al [10] introduced the separation between ownership and management in the fashion of Fershtman and Judd [11], Sklivas [12], and Vickers [13] into in the models of Ogawa [6] and Bárcena-Ruiz and Garzón [7].…”
Section: Introductionmentioning
confidence: 97%